2021
DOI: 10.2196/26808
|View full text |Cite
|
Sign up to set email alerts
|

Leisure and Problem Gaming Behaviors Among Children and Adolescents During School Closures Caused by COVID-19 in Hong Kong: Quantitative Cross-sectional Survey Study

Abstract: Background School closures during the COVID-19 pandemic may have exacerbated students’ loneliness, addictive gaming behaviors, and poor mental health. These mental health issues confronting young people are of public concern. Objective This study aimed to examine the associations between loneliness and gaming addiction behaviors among young people in Hong Kong and to investigate how familial factors, psychological distress, and gender differences modera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
91
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 56 publications
(53 reference statements)
8
91
0
1
Order By: Relevance
“…Parents may need to work longer to secure a job and maintain the daily necessities for the family [ 44 ]. The holistic quality of life of students in low-income families is more likely to be threatened [ 45 ] and their risk of psychosocial problems and problem behaviors is higher [ 15 , 46 ]. For example, inadequate digital devices and unsatisfactory internet access may limit their social connection with peers and teachers, limit the access to health-related information and knowledge, and increase risks of exposure to gaming temptation during lockdown [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents may need to work longer to secure a job and maintain the daily necessities for the family [ 44 ]. The holistic quality of life of students in low-income families is more likely to be threatened [ 45 ] and their risk of psychosocial problems and problem behaviors is higher [ 15 , 46 ]. For example, inadequate digital devices and unsatisfactory internet access may limit their social connection with peers and teachers, limit the access to health-related information and knowledge, and increase risks of exposure to gaming temptation during lockdown [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The holistic quality of life of students in low-income families is more likely to be threatened [ 45 ] and their risk of psychosocial problems and problem behaviors is higher [ 15 , 46 ]. For example, inadequate digital devices and unsatisfactory internet access may limit their social connection with peers and teachers, limit the access to health-related information and knowledge, and increase risks of exposure to gaming temptation during lockdown [ 46 ]. Families trapped in smaller apartment may have greater difficulties of maintaining life quality [ 45 ] especially for low SES families.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, anxiety was found to be a predictor for online videogame and addiction [ 19 ], and a study from Japan indicated an increased prevalence of IGD, especially in the younger population [ 20 ]. In addition, one study from Hong Kong indicated that female children and adolescents felt more loneliness during the pandemic, while showing a significant relationship between loneliness and gaming addiction [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 caused rising infection rates and prompted variable lockdown measures, including three waves of lockdown in the UK (March 2020, November 2020, and January–April 2021) [ 156 ] with considerable negative psychosocial implications (i.e., worry, stress, helplessness) for young people [ 157 ] and mental health impacts such as depression and anxiety [ 158 ]. COVID-19-related distress impacted young people directly or indirectly in several ways, through disruption of individuals’ activities, the enforcement of restrictions, the closing of schools, the challenges of online learning, health problems, and lack of face-to-face social or physical activity and play [ 159 ]. This prolonged period of isolation and restriction of real life interactions led to an increased reliance on screen time [ 160 ] and recreational online activities, such as gaming and social media use to maintain social connections [ 161 ] or for escapism [ 162 ], posing risks for more vulnerable young people [ 163 ].…”
Section: Discussionmentioning
confidence: 99%